Efektivitas LKPD Berbasis Inkuiri untuk Meningkatkan Kemampuan Komunikasi IPA Peserta Didik - Wahyudi, Zulfa Zachri; Salsabila, Khalis; Khairiyah, Nadiyah; Siagian, Nursaidah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to test the effectiveness of inquiry-based student worksheets in improving students' science communication skills. The research design used in this study is a quasi-experimental design. The research population consists of fourth-grade students in a private school for the academic year 2022/2023. One class, specifically class IV A, was chosen as the sample from the two available classes. Data collection techniques in this study were conducted through interviews, tests, and observations. The research instruments used were (1) research instruments including the learning implementation plan, and (2) data collection instruments including test instruments in the form of pre-test and post-test evaluation sheets. The communication skills gain index obtained in class IV A was 0.79 or 79.49%. Furthermore, the N-Gain Score of 0.79 is categorized as high because the N-Gain Score of 0.79 > 0.7. Therefore, the improvement in students' science communication skills using inquiry-based student worksheets is considered high, meaning that students' science communication skills using inquiry-based student worksheets have significantly improved compared to before the learning process.